Presenilins mediate a dual intramembranous γ-secretase cleavage of Notch-1 - Okochi, Masayasu (Oxford University Press, 2002)
Following ectodomain shedding, Notch-1 undergoes presenilin (PS)-dependent constitutive intramembranous endoproteolysis at site-3. This cleavage is similar to the PS-dependent γ-secretase cleavage of the β-amyloid precursor protein (βAPP). However, topological differences in cleavage resulting in amyloid β-peptide (Aβ) or the Notch-1 intracellular domain (NICD) indicated independent mechanisms of proteolytic cleavage. We now demonstrate the secretion of an N-terminal Notch-1 Aβ-like fragment (Nβ). Analysis of Nβ by MALDI-TOF MS revealed that Nβ is cleaved at a novel site (site-4, S4) near the middle of the transmembrane domain. Like the corresponding cleavage of βAPP at position 40 and 42 of the Aβ domain, S4 cleavage is PS dependent. The precision of this cleavage is affected by familial Alzheimer’s disease-associated PS1 mutations similar to the pathological endoproteolysis of βAPP. Considering these similarities between intramembranous processing of Notch and βAPP, we conclude that these proteins are cleaved by a common mechanism utilizing the same protease, i.e. PS/γ-secretase.